Virtual reality in the treatment of anxiety and chronic neuropathic pain. Preliminary study - J Muriel-Fernández; C Muriel Villoria; MJ Sánchez Ledesma; JM Gonçalves Estella; JM López Millán (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
Background: Pain and anxiety caused by prolonged treatment of neuropathic pain can result in discomfort for patients. Virtual Reality (VR) is a technology that is capable of entertaining and distracting the user. Among its many applications, we find the improvement of pain management and the reduction of anxiety in patients undergoing medical treatment. Objective: We aim to publish the protocol of a clinical trial for the reduction of pain and anxiety after a couple of VR sessions in patients with neuropathic pain that is difficult to treat. Methods: An observational, analytical, and prospective study was conducted. Virtual Reality (VR) was employed as a technique aimed at reducing pain and anxiety, twice a week for 30 days, as a complement to pharmacological treatment. Pain was assessed using the 'Pain Detect' questionnaire and the Visual Analog Scale (VAS), while anxiety was evaluated through the Goldberg Scale. Results: The preliminary results indicate that immersive virtual reality therapy is a promising alternative treatment for challenging-to-treat neuropathic pain. Without side effects, an appealing feature of VR therapy. Conclusion: Virtual reality can be a useful tool for patients who present with neuropathic pain that is resistant to conventional treatments that generate pain and anxiety.